Testing Automation of Context-Oriented Programs Using Separation Logic - Mohamed A. El-Zawawy (Applied Computational Intelligence and Soft Computing)
A new approach for programming that enables switching among contexts of commands during program execution is context-oriented programming (COP). This technique is more structured and modular than object-oriented and aspect-oriented programming and hence more flexible. For context-oriented programming, as implemented in COP languages such as ContextJ* and ContextL, this paper introduces accurate operational semantics. The language model of this paper uses Java concepts and is equipped with layer techniques for activation/deactivation of layer contexts. This paper also presents a logical system for COP programs. This logic is necessary for the automation of testing, developing, and validating of partial correctness specifications for COP programs and is an extension of separation logic. A mathematical soundness proof for the logical system against the proposed operational semantics is presented in the paper.